Hydrodynamic Cavitation for Industrial Wastewater Treatment: A Review of Efficiency, Mechanisms, and Hybrid Approaches - Prachi Trivedi; Ayushi Solanki; Dr. Krunal Patel (International Journal of Scientific Research in Civil Engineering, 2025)
Hydrodynamic cavitation (HC) has emerged as a highly promising advanced oxidation process (AOP) for the effective degradation of a wide range of persistent pollutants found in industrial wastewater. This review critically examines the underlying mechanisms, operational parameters, and treatment efficiencies associated with HC-based processes, with particular emphasis on their application in the textile, pharmaceutical, and synthetic organic chemical industries. The study highlights the enhanced pollutant degradation achieved through hybrid systems that integrate HC with complementary techniques such as ozonation. Reactor design variations—including venturi tubes, orifice plates, and rotational devices—are discussed in the context of energy efficiency and cavitation intensity. Key pollutants such as dyes, active pharmaceutical ingredients (APIs), and recalcitrant organics are evaluated in terms of decolorization, COD reduction, and improved biodegradability. Furthermore, a techno-economic assessment of HC-based hybrid systems is presented, outlining both the operational advantages and current limitations. The review concludes by identifying future research directions aimed at optimizing process variables and facilitating the large-scale deployment of HC technologies for sustainable and cost-effective industrial wastewater treatment.